2017
DOI: 10.1123/jmld.2016-0041
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Mechanisms Underlying the Effects of an Incidental Choice on Motor Learning

Abstract: The present study investigated whether motivation and augmented feedback processing explain the effect of an incidental choice on motor learning, and examined whether motivation and feedback processing generally predict learning. Accordingly, participants were assigned to one of two groups, choice or yoked, then asked to practice a nondominant arm beanbag toss. The choice group was allowed to choose the color of the beanbag with which they made the toss, whereas the yoked group was not. Motor learning was dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
26
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(32 citation statements)
references
References 0 publications
5
26
1
Order By: Relevance
“…However, on the transfer test, the Good KR and Low SE group had higher accuracy scores than the other three groups. These results are in line with previous studies in which enhanced expectancies benefitted motor performance and motor learning ( Avila, Chiviacowsky, Wulf, & Lewthwaite, 2012; Badami et al, 2012;Chiviacowsky & Wulf, 2007;Chiviacowsky et al, 2009;Ghorbani, 2019;Gonc¸alves et al, 2018;Grand, Daou, Lohse, & Miller, 2017;Lessa et al, 2018;Montes, Wulf, & Navalta, 2018;Ong & Hodges, 2018;Pascua, Wulf, & Lewthwaite, 2015;Saemi et al, 2011Saemi et al, , 2012Stoate, Wulf, & Lewthwaite, 2012;Wulf et al, 2014), but they extend these findings to suggest a particular benefit for individuals with low SE ratings. In addition, our results showed that during acquisition, KR from good trials did not (further) increase SE of participants in Good KR and High SE group (see Figure 2), as these participants simply maintained their initially high level of SE during acquisition.…”
Section: Discussionsupporting
confidence: 91%
“…However, on the transfer test, the Good KR and Low SE group had higher accuracy scores than the other three groups. These results are in line with previous studies in which enhanced expectancies benefitted motor performance and motor learning ( Avila, Chiviacowsky, Wulf, & Lewthwaite, 2012; Badami et al, 2012;Chiviacowsky & Wulf, 2007;Chiviacowsky et al, 2009;Ghorbani, 2019;Gonc¸alves et al, 2018;Grand, Daou, Lohse, & Miller, 2017;Lessa et al, 2018;Montes, Wulf, & Navalta, 2018;Ong & Hodges, 2018;Pascua, Wulf, & Lewthwaite, 2015;Saemi et al, 2011Saemi et al, , 2012Stoate, Wulf, & Lewthwaite, 2012;Wulf et al, 2014), but they extend these findings to suggest a particular benefit for individuals with low SE ratings. In addition, our results showed that during acquisition, KR from good trials did not (further) increase SE of participants in Good KR and High SE group (see Figure 2), as these participants simply maintained their initially high level of SE during acquisition.…”
Section: Discussionsupporting
confidence: 91%
“…Studies with drop-outs reported the losses adequately. 49,5254 In summary, the analyses of the methodological quality and risk of bias revealed a tight range of methodological issues and indicated a moderate to strong quality within the appraised approaches. Taking the identified limitations into account, the systematically collected studies thus provide a useful basis capable of informing responsible actors in (competitive) sports and future research.…”
Section: Resultsmentioning
confidence: 95%
“…The dates of publication ranged from 1995 to 2018, with a clear focus on the last four years. Seventeen studies were conducted in the USA, 42,45,46,50,5465 six in Brazil, 41,47,6669 four in Germany, 51,7072 two in Canada, 52,53 and one each in Spain 40 and Korea. 48 In total, 1273 participants were included in the 31 trials, at least 644 were females (about 51%; two studies made no specification regarding gender).…”
Section: Resultsmentioning
confidence: 99%
“…Although it is unlikely that individual differences in random allocation explain all the group differences seen in the literature, it is possible that they might explain some of the positive results. In at least two other motor learning studies, measures of motivation (which is expected to mediate success perception effects) were shown to be unrelated to retention outcomes [37,38].…”
Section: Discussionmentioning
confidence: 99%